Study on Eco-Friendly Underground Mining System for Ultra-Thick Coal Seams in Thailand - Takashi Sasaoka (International Conference on Ground Control in Mining, 2011)
EGAT Mae Moh Lignite Mine in Thailand produces about 16 million tons of lignite annually from open-cut mining. The coal is used to generate 2,400 MW of electricity. In the near future, however, the coal must be extracted from underground at 400? 500 m (1,312?1,640 ft) deep from the surface. The problem is the thickness of the coal seams. There are two coal seams that are about 25 m (82 ft) thick with 20?25 m (66?82 ft) of interburden between them. Up to now, many mining systems for thick coal seams have been used and improved in the world. However, where the thickness of coal seams is beyond the limitation of the current mining technology and system, an applicable mining system has to be introduced, considering influencing factors such as caving and subsidence. In order to investigate thick seam mining systems and propose a new mining system in ultra-thick coal seams in Thailand, a joint research group was established by Japanese and Thai researchers and mining engineers in early2009. This paper describes underground mining systems for thick coal seams and proposes an innovative underground mining system for thick coal seam, ?eco-friendly underground mining system?, considering geological, geotechnical, and environmental conditions in this mine. This paper discusses its applicability to this mine by means of numerical analysis from the geotechnical point of view.